Novel circuit to compensate the effect of source open circuit fault in distributed generation system - Maged N. F. Nashed; Mona N. Eskander (Energy Reports, 2020)
In this paper a novel compensating circuit, composed of capacitors, one IGBT switch, and a diode bridge is designed and employed within a SOFC distributed generation system connected to a micro-grid. The DG system consists of the FC stack, a Cuk converter, a three phase inverter, the proposed compensating circuit, and Type 2 Fuzzy logic controller to adjust the output voltage to its reference value, to manage the charging of the compensating circuit capacitors during normal operation, and to manage the discharge of the compensating circuit during fault to ensure the continuous power supply to the load during the open circuit fault of the SOFC. A detailed description of the managing controllers and switching sequences is also given. Results proved the validity of the compensating circuit in supplying the load during the absence of the main source, hence preventing serious consequences of shutting down important loads.
Keywords: 330; Compensating circuit; Cuk converter; Grid; Type 2 fuzzy logic controller